Wesentliche Fakten zur 'Investitionsschwäche' in Deutschland - Bastian Alm; Martin Meurers (Wirtschaftsdienst, 2015)
Deutschland wird von Teilen der Wissenschaft, der Politik und in der Öffentlichkeit Investitionsschwäche attestiert. Doch tatsächlich trifft dies nicht auf alle Bereiche der Investitionsentwicklung in Deutschland zu. Die Autoren arbeiten unterschiedliche Trends auf verschiedenen staatlichen Ebenen und in einzelnen Wirtschaftsbereichen heraus und untersuchen, inwieweit die Investitionstätigkeit auf den Konjunkturverlauf reagiert und was das Investitionsverhalten von Unternehmen bestimmt. – – Widely independent from the specific economic structure of a country, investment is indispensable for economic development. Against this background, backlogs in private and public investment, especially in fields which are critical for future growth, are often seen as a cause for concern. This paper deals with the development of private and public investment activity in Germany since 1991. Using a probit model, we observe for small and medium-sized businesses that their probability of investing seems to increase with higher profit margins, equity capital ratios and employment growth, as well as with better business expectations.
Keywords: C29; H54; O16; 330; Investition; Konjunktur; Deutschland